Reestructuración del proceso de compras en la unidad de abastecimiento petroindustrial Quito, filial de Petroecuador - Melena Heredia, Adriana Graciela (2006)
This study has been performed in order to analyze the times involved different existing activities within a purchasing process that takes place in Supply Unit Petroindustrial Quito, for the respective procurement of materials, supplies, parts and accessories, spare parts and equipment for users of Quito and 3 refineries by Petroindustrial, a subsidiary of Petroecuador.